Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 234: 47



Work Step by Step

We use the distributive property and then isolate the variable on one side of the equation to obtain: $-3(x-1)+2(x+3)=-4$ $-3x+3+2x+6=-4$ $-3x+2x+6+3=-4$ $-x+9=-4$ $-x=-4-9$ $-x=-13$ $x=13$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.